The dark and bright side of network complexity: Novel insights from an asymmetric supply chain recovery and disruption approach - Emmanuel Asafo-Adjei; Zulaiha Hamidu; Kassimu Issau; Baba Adibura Seidu; Anokye M. Adam (Cogent Business & Management, 2023)
Recent studies have conceptualized the potential for a dark and bright perspective of network complexity in relation to supply chain disruption and resilience respectively. Few empirical studies have been conducted on the relationship among supply chain network complexity, supply chain disruption and supply chain resilience. However, prior studies have not yet investigated how different measures of network complexity relate to both resilience strategies and disruption. The current study, therefore, examines the dark and bright side of supply chain network complexity dimensions using supply chain disruption (SCD) and three supply chain resilience (SCR) strategies (collaboration, flexibility and redundancy) as endogenous variables. The dimensions of the supply chain network complexity utilised in this study are-supply complexity (SNC), customer complexity (CNC), and logistics complexity (LNC) whereas the three SCR strategies considered included; collaboration, flexibility and redundancy. The study uses PLS-SEM and a sample of 690 manufacturing firms in Accra Metropolis. Results show that supply complexity has a positive relationship with both disruption and resilience strategies, while customer complexity is only related to disruption, and logistics complexity is related to all resilience strategies. The study provides theoretical, practical, and political implications.
Keywords: 650; asymmetric approach; logistics complexity; supply chain disruption; supply chain resilience; Supply complexity; customer complexity